HUBUNGAN MOTIVASI DAN DISIPLIN BELAJAR DENGAN HASIL BELAJAR SENI RUPA SISWA SMPN 34 PADANG - Mel Pitasari; Eswendi Eswendi (Universitas Negeri Padang, 2020)
The research aimed to find out whether there. is a significant. Relationship, between: (1) The motivation to learn with the results of art learning, (2) Learning discipline with the outcomes of art learning (3) Motivation and discipline to learn together with Learning results,of art students of SMPN 34 Padang. The source of this research data is the student sample research. Data is collected using polls and documentation. Research findings show that (1) there is a significant.link between the motivation for learning with the results of art learning with rxy = 0.252, (2) There is a significant relationship between the discipline of learning with the results of learning the art of students with rxy = 0.253, (3) There is a significant.link between the motivation and discipline of learning fine art together with the results learning art of students with rxy = (0.276), the entire price of rxy count greater than rxy table of 0.183.Kata kunci : Motivasi Belajar, Seni Rupa, Disiplin Belajar, Hasil Belajar.